Hermeneutics of hadith about music: Fazlur Rahman dan Khaled M. Aboue el Fadl - Wafi, Hibatul; Na Ziihah, Rahil Ayu; Arifin, Zainal; Mujahidah, Filyatul (Institut Agama Islam Negeri (IAIN) Curup, 2024)
Hadith regarding music in the neomodern era became the focus of Muslims, where there were many negative things or deviated from Muslims in consuming music so many Muslims assumed that consuming music in life was something that was unlawful. Using the hermeneutical approach of Fazlur Rahman and Khalid about El-Fadl, a study will be carried out to interpret hadiths about music. This research is a literature review that aims to interpret the hadith about music with the hermeneutics of Fazlur Rahman and Khalid about El-Fadl. The primary source in this research is the hadith about music. In addition, the secondary sources used are in the form of several books and journal articles that have the same research focus. Reinterpretation of hadith based on Fazlur Rahman and Khalid M. Aboue El-Fadl's hermeneutics is generally carried out with three aspects, namely the meaning of hadith texts, a socio-historical approach and interpretation of hadiths. The result of the reinterpretation of the hadith about music is to provide a law that music is permissible within the limits of Islamic law.